2012
DOI: 10.1111/j.1525-1314.2012.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of metamorphism, melting and exhumation of the Leo Pargil dome, northwest India

Abstract: The Leo Pargil dome, northwest India, is a 30 km‐wide, northeast‐trending structure that is cored by gneiss and mantled by amphibolite facies metamorphic rocks that are intruded by a leucogranite injection complex. Oppositely dipping, normal‐sense shear zones that accommodated orogen‐parallel extension within a convergent orogen bound the dome. The broadly distributed Leo Pargil shear zone defines the southwest flank of the dome and separates the dome from the metasedimentary and sedimentary rocks in the hangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 108 publications
(359 reference statements)
3
105
0
Order By: Relevance
“…These exhumation rates, as well as the inferred cooling rates, could also be reconciled with tectonically driven exhumation, such as in a gneiss dome/core complex, thrust sheet or mid‐crustal channel (e.g. Gordon, Whitney, Teyssier, Grove, & Dunlap, ; Langille, Jessup, Cottle, Lederer, & Ahmad, ; Spear & Parrish, ; Stevens et al., ). However, the apparent absence of suitable major shear zones in the eastern Beartooth Mountains may suggest that rapid HT decompression was not driven by tectonic extrusion, although we cannot rule out this possibility.…”
Section: Potential Mechanisms For Ht Metamorphismmentioning
confidence: 82%
“…These exhumation rates, as well as the inferred cooling rates, could also be reconciled with tectonically driven exhumation, such as in a gneiss dome/core complex, thrust sheet or mid‐crustal channel (e.g. Gordon, Whitney, Teyssier, Grove, & Dunlap, ; Langille, Jessup, Cottle, Lederer, & Ahmad, ; Spear & Parrish, ; Stevens et al., ). However, the apparent absence of suitable major shear zones in the eastern Beartooth Mountains may suggest that rapid HT decompression was not driven by tectonic extrusion, although we cannot rule out this possibility.…”
Section: Potential Mechanisms For Ht Metamorphismmentioning
confidence: 82%
“…For example, the Gurla Mandhata detachment system (the Pulan shear zone and the STD in this study) may account for ~20 km in exhumation and up to 60 km slip in the Gurla Mandhata dome [ Murphy et al ., ]. Exhumation of the Ama Drime massif in Tibet‐Nepal [ Jessup et al ., ; Cottle et al ., ; Leloup et al ., ] and the Leo Pargil dome in NW India [ Thiede et al ., ; Langille et al ., ] was kinematically linked to the orogen‐parallel extension along its two bounding shear zones with opposite shear senses. In this case, the geometry is similar to that of a metamorphic core complex, while the shear sense is opposite on the two sides of the dome.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, orogen‐parallel stretching lineation has been observed in a few areas in the upper part of the GHC, including the Nyalam area in southern Tibet [ Brun et a l., ], central Nepal [ Pêcher , ; Pêcher et al ., ; Coleman , ], and Garhwal [ Pêcher and Scaillet , ] and Ladakh areas in the western Himalaya [ Epard and Steck , ]. Orogen‐parallel ductile detachments were also recognized at the roofs of transverse domes deforming or cutting across the STD, e.g., in the Gurla Mandhata area in SW Tibet [ Murphy et al ., ], the Leo Pargil dome in NW India [ Thiede et al ., ; Langille et al ., ], and the Ama Drime massif in Tibet‐Nepal [ Jessup et al ., ; Langille et al ., ]. The timing, mechanisms, and regional significance of the orogen‐parallel ductile deformation for exhumation of the GHC are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of monazite grain-scale age domains have demonstrated that they are commonly associated with distinct Y and heavy rare earth element (HREE) zones (e.g., Foster et al, 2000Foster et al, , 2002Gibson et al, 2004;Cottle et al, 2009;Kellett et al, 2010;Larson et al, 2011;Langille et al, 2012). The variable composition of monazite grains can be interpreted as a function of interactions with and the growth/presence/ consumption of garnet and other accessory phases that incorporate HREEs and Y (Pyle and Spear, 1999;Foster et al, 2000;Gibson et al, 2004;Buick et al, 2006;.…”
Section: Petrochronologic Interpretationmentioning
confidence: 99%